Magnetic and acoustic properties of CoCr2S4 - Felea, V.; Cong, P.T.; Prodan, L.; Gritsenko, Y.; Wosnitza, J.; Zherlitsyn, S.; Tsurkan, V. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2017)
We report results of magnetic and ultrasound studies of the sulfide spinel CoCr2S4, for which the multiferroicity has recently been suggested. Clear anomalies in the magnetic and acoustic properties have been observed at TN = 222 K and in applied magnetic fields evidencing the important role of magnetoelastic interactions in this material. In contrast, no anomalies have been detected at TC = 28 K, where a spontaneous electric polarization and isostructural distortions have been reported. We have extracted the H–T phase diagram of CoCr2S4 from our experiments for magnetic fields applied along the direction. We discuss our observations in relation to our earlier results obtained for the oxide multiferroic spinel CoCr2S4.